2008
DOI: 10.1680/geng.2008.161.1.49
|View full text |Cite
|
Sign up to set email alerts
|

CFA pile behaviour in very stiff lodgement till

Abstract: The design of CFA piles in the stiff/hard lodgement till that underlies most of Dublin is usually based on published experience from similar piles in other soils that lack the high density and stiffness of this till. The results of load tests on two instrumented test piles are presented, one 450 mm in diameter and 12·3 m long and the other 600 mm in diameter and 11 m long, which were loaded to 3·15 MN and 4·5 MN respectively. A 1 m long instrumented dummy pile was formed at the same time as the prototype and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…From a series of model tests, Kassem et al [2] observed that the axial capacity of CFA piles is approximately twice of that of bored piles, which is attributed to an increase of the pile diameter by the high-pressure pumping of concrete and a higher interface roughness caused by auger rotation. Farrell et al [7] reported a shaft resistance of 230 kPa in lodgement till, which was of a similar magnitude of the driven pile. Such a finding contradicts the viewpoint of O'Neill [15], in which the bearing capacity of driven piles excels significantly over that of augered piles.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…From a series of model tests, Kassem et al [2] observed that the axial capacity of CFA piles is approximately twice of that of bored piles, which is attributed to an increase of the pile diameter by the high-pressure pumping of concrete and a higher interface roughness caused by auger rotation. Farrell et al [7] reported a shaft resistance of 230 kPa in lodgement till, which was of a similar magnitude of the driven pile. Such a finding contradicts the viewpoint of O'Neill [15], in which the bearing capacity of driven piles excels significantly over that of augered piles.…”
Section: Introductionmentioning
confidence: 82%
“…He found that the shaft resistance is independent of the relative density of sand, but strongly correlated to the cone penetration test (CPT) or standard penetration test (SPT) result. Other works were extended to soft clay [5], silty soil [6], lodgement till [7], and mixed soil [8]. Moreover, Pession and Tsuha [9] has developed a CFA-based energy pile and examined its in-field performance with different configurations in layered soil.…”
Section: Introductionmentioning
confidence: 99%
“…In the CFA pile construction, the grouting is injected direct after excavation of a borehole in the CFA pile and hence the soil collapse can be minimized by confining of grouting in the borehole. Since the CFA pile is mainly constructed on weak ground conditions, studies have been conducted to estimate the bearing capacity and the behavior of CFA piles in various grounds (Farrell and Lawler, 2008, Gavin et al, 2009, Battista et al, 2016, Loveridge and Cecinato, 2016). In the CFA pile, the loss of ground can affect the bearing capacity of the pile (Leznicki et al, 1992 [8]).…”
Section: Introductionmentioning
confidence: 99%